Absorpsi Tari Bedhaya Bedhah Madiun Gaya Yogyakarta di Mangkunegaran Masa Pemerintahan Mangkunegara VII - S. Sriyadi; Pramutomo R.M. (Department of History, Faculty of Humanities, Diponegoro University, 2020)
The history of dance in Mangkunegaran is basically using the Surakarta style. During the reign of Mangkunegara VII there was the dance called Bedhaya Bedhah Madiun dance with Yogyakarta style. This study tries to describe the factors of Yogyakarta dance style in Pura Mangkunegaran by choosing a specific dance called Bedhaya Bedhah Madiun. This is ethnochoreologiy research using the historical approach. The existence of the Bedhaya Bedhah Madiun dance in Pura Mangkunegaran is mostly influenced by the social and political demands of Mangkunegaran. As the top of the social and political hierarchy in Mangkunegaran, Mangkunegara VII' has policy impacts on the budgetary of the Bedhaya Bedhah Madiun dance in Mangkunegaran. The most challenging policy is the political nuance which is carried out with the Yogyakarta Sultanate Palace. Mangkunegara VII's marriage to Gusti Timur was blessed with a daughter, who is confirmed by her ability in dancing bedhaya and srimpi. Around 1934 Gusti Nurul was permitted to be sent to Krida Beksa Wirama to study the dance bedhaya and srimpi Yogyakarta style. One of the learning materials is the Bedhaya Bedhah Madiun dance, which is then presented at Pura Mangkunegaran.